PENGARUH TERAPI REMINISCENCE TERHADAP KECEMASAN PADA LANSIA DI KELURAHAN BAILANG - Dwisetyo, Bayu; Monoarfa, Andriyanto (Jurnal Ilmu Keperawatan Komunitas, 2025)
Anxiety is a person's psychological condition that is full of fear and worry, where feelings of fear and worry about something that is not certain will happen. The purpose of this research is to determine the effect of reminiscence therapy on anxiety in the elderly in Bailang Village, Environment V, Bunaken District. This research design is quasi-experimental and the type of research used in this research is (One Group Pre-Post Test Design). The sample was taken based on the number of 15 elderly respondents using purposive sampling based on inclusive and exclusive criteria. Data collection was carried out by means of direct interviews with respondents and filling out questionnaires. Furthermore, the data that had been collected using computer assistance with data processing applications and statistical tests was analyzed using the Wilcoxon test with a significance level (α) of 0.05. The results of research using the Wilcoxon Test showed that the ρ value was smaller than the significant value of (0.000<0.05). The results of this research showed that it was found that Ha was accepted and H0 was rejected. The conclusion of the research is that there is an effect of Reminiscence Therapy on Anxiety in the Elderly in Bailang Village, Environment V, Bunaken District. The results of this research are expected to provide input and development of knowledge, especially reminiscence therapy to reduce the anxiety level of the elderly.